Sensory discrimination tests and measurements : statistical principles, procedures, and tables - Bi, Jian, 1949- (Wiley Blackwell, 2015)
Sensory testing and measurement are the main functions of sensory analysis. In recent years, the sensory and consumer field has evolved to include both difference testing and similarity testing, and new sensory discrimination methods such as the tetrads have received more attention in the literature. This second edition of Sensory Discrimination Tests and Measurements is updated throughout and responds to these changes and includes: A wide range of sensory measurements: Measurements of sensory effect (d', R-index and Gini-index); Measurements of performance of trained sensory panel (Intrac.